An Improved Calculation Method of Coal Consumption Index for Heating in CHP with a High Back Pressure Turbine. Issue 1 (February 2021) - Sun, Jian; Ma, Shicai; Huo, Cheng; Ge, Zhihua; Zhou, Shaoxiang
Abstract: CHP (combined heating and power) system is playing an important role for district heating, meanwhile, the latent heat of exhausted steam at the thermal power plant is discharged to atmosphere directly, which is often more than 30%. Waste heat recovery is of great significance for reducing coal consumption indicators for heating in CHP system. The method by replacing different rotors of the LP (low pressure) cylinder is presented and experimented with a 140MW turbine, whose exhausted steam could be recovered completely. Besides, an improved calculation method of coal consumption index for heating is discussed. The improved mathematical model is used to calculate the influence of exhaust pressure on steam turbine power generation efficiency, which improves the accuracy of heating coal consumption. This experimented coal consumption index for heating is 12.7 kgce/GJ, which is much lower than the traditional CHP system (20 kgce/GJ).